2021
DOI: 10.3390/cancers13153909
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Other Non-Coding RNAs in Epstein–Barr Virus-Associated Cancers

Abstract: EBV is a direct causative agent in around 1.5% of all cancers. The oncogenic properties of EBV are related to its ability to activate processes needed for cellular proliferation, survival, migration, and immune evasion. The EBV latency program is required for the immortalization of infected B cells and involves the expression of non-coding RNAs (ncRNAs), including viral microRNAs. These ncRNAs have different functions that contribute to virus persistence in the asymptomatic host and to the development of EBV-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 245 publications
(306 reference statements)
1
10
0
Order By: Relevance
“…Cellular lncRNAs can be differentially induced by EBV infection. The dysregulated lncRNAs probably modulate tumorigenesis and other biological functions (28)(29)(30). Our result is consistent with others' reports that SNHG8 is associated with the progression in multiple types of cancer in the liver, colon, lung, ovary, prostate, esophagus, and so on (15,(31)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 92%
“…Cellular lncRNAs can be differentially induced by EBV infection. The dysregulated lncRNAs probably modulate tumorigenesis and other biological functions (28)(29)(30). Our result is consistent with others' reports that SNHG8 is associated with the progression in multiple types of cancer in the liver, colon, lung, ovary, prostate, esophagus, and so on (15,(31)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, various mirs have been confirmed to exhibit prognostic value in a variety of human cancers, and a great many of mirs have also been proved acting as a co-effector with other elements in tumor progression such as: cellular proliferation, survival, migration, and immune evasion. Thus, the mirs play an important role in the field of malignant tumor ( 10 ). The study by Zhao et al ( 44 ), showed that mir-375 not only reduced the stemness, but also decreased adriamycin resistance of breast cancer cells, indicating that mir-375 may inhibit the stemness breast cancer cells by targeting JAK2.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNA plays a vital role in cancer biology and provides potential targets for cancer intervention ( 8 , 9 ). Early studies had indicated that non-coding RNA had the potential clinical utility for diagnosing and prognosticating cancers ( 10 ). One type of non-coding RNA is called micro-RNA (mir), which ranges in size from 20-24 nucleotides ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…EBV miRNAs’ diagnostic value as clinical biomarkers for the detection for the EBV-associated development of various tumours has not yet been clinically applied. The main challenges for the use of EBV miRNAs in the clinical setting revolves around identifying unique or common v-miRNAs that can be used as specific biomarkers for various cancers [ 216 ]. Such challenges require large-scale clinical studies to elucidate and verify their translation and application in clinical settings.…”
Section: Challenges and Opportunities Of V-mirnas Use In Theranostics...mentioning
confidence: 99%